Prospek Pengembangan Pola Tanam dan Diversifikasi Tanaman Pangan di Indonesia - I Wayan Rusastra; Handewi Purwati Saliem; nFN Supriyati; nFN Saptana (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2004)
EnglishAgricultural diversification policy has been developed since 1975 with the aim of strengthening food self-sufficiency program. This policy is followed up by research and development on cropping patterns in various agro-ecosystems with the target of providing know-how and locally specific technologies. In the future, it is necessary to evaluate potencies, impacts, constraints, and development prospect of the diversification program. Recommended cropping patterns in terms of higher production and income are not sustainable. Some required supporting policies are supply of seeds of secondary and vegetables crops, development program credit, labor-saving technology, coordinated supply of irrigation water, and extension improvement. At national level, it is necessary to develop physical infrastructure and agro-industry institution mainly for secondary and vegetable crops as the strategic precondition for agricultural diversification acceleration.IndonesianKebijakan diversifikasi usahatani telah dikembangkan sejak tahun 1975 dalam rangka memantapkan program swasembada pangan. Kebijakan ini ditindaklanjuti dengan penelitian dan pengembangan pola tanam pada berbagai agroekosistem, dengan sasaran penyediaan teknologi tepat guna spesifik lokasi. Pengembangan diversifikasi ini perlu dievaluasi potensi, dampak, kendala dan prospek pengembangannya di masa depan. Potensi pola tanam rekomendasi dalam bentuk tingkat produksi dan pendapatan yang lebih tinggi dalam pengembangannya ternyata tidak berkelanjutan. Beberapa kebijakan pendukung yang diperlukan adalah penyediaan bibit palawija dan sayuran, kredit program pengembangan, teknologi hemat tenaga kerja, koordinasi penyediaan air irigasi, dan peningkatan kinerja penyuluhan. Pada tataran makro dibutuhkan pengembangan infrastruktur fisik dan kelembagaan agroindustri (palawija dan sayuran) sebagai prakondisi strategis akselerasi diversifikasi pertanian.